Kapasitas Kapasitor Koreksi Faktor Daya Pada Pelanggan Rumah Tangga 6600 VA - Ibnu Hajar; Safira Nabilla Julianti (Sekolah Tinggi Teknik - PLN, 2021)
It is undeniable that the low value of the power factor can cause problems with the electrical load in the form of power consumed that does not match the installed power. A low power factor can cause power usage to be less than optimal and current increase so that it can result in increased heat losses in the cable. From the data, there are still many customers who have a power factor of 0.5 to 0.7 meaning they are below the standard, for this reason it is necessary to improve the power factor value by installing capacitors where it is necessary to calculate the capacitor’s capacity according to the installed power, so as to optimize the distribution of funds and reduce heat losses from the conductor so that the distribution condition is more stable. The diagram method is used, a diagram showing the kVAR value is needed before and after compensation. With the improvement of the power factor in accordance with the standard, a more optimal use of electric power is obtained. From the results of the calculations, the average capacity of the capacitor used for household customers with a power of 6600 VA is or 37.4 F.